A review of the sources, distribution sequences, and health risks associated with exposure to atmospheric polycyclic aromatic hydrocarbons. Issue 1 (31st December 2023) - Safo-Adu, Godfred; Attiogbe, Francis; Emahi, Ismaila; Ofosu, Francis Gorman
Abstract: Atmospheric polycyclic aromatic hydrocarbons (PAHs) are associated with adverse health effects in exposed populations. Understanding PAH pollution in ambient air and its adverse impacts is essential for developing effective actions for combating air pollution. This review paper summarised and discussed the findings of research work that determined the concentrations, distribution sequence, and health risk exposure levels of atmospheric PAHs in cities worldwide. It also gave an overview of the sources and the methodology for appraising the health risk of exposure to atmospheric PAHs. Eighty-five articles published in peer-reviewed journals from 2010 to 2023 were identified in academic research databases, with 55 reporting on sources and distribution of atmospheric PAHs, while 30 evaluated the health risk of exposure to PAHs in ambient air. The narrative review approach was employed to critically analyse and produce descriptive summaries of distribution patterns and health risk exposure levels of atmospheric PAHs in a tabular form. The review showed that the total PAH concentration in urban areas was about eight times greater than in rural environments and emanated from diverse sources. However, vehicle exhaust and industrial emissions were the primary sources of atmospheric PAHs. The distribution sequence of PAHs in particulate and gas phases was HMW>MMW>LMW PAHs and LMW>MMW>HMW PAHs, respectively. Chronic exposure to PAHs in the environment increased the risk of asthma, cardiovascular disease, and lung cancer. Adoption of stricter emission standards, cleaner energy sources, and more efficient industrial technology will aid in the reduction of particulate PAH pollution and its negative health consequences in urban areas.